Preventing Ischial Pressure Ulcers: I. Review of Neuromuscular Electrical Stimulation - Hilton M. Kaplan; Gerald E. Loeb (Applied Bionics and Biomechanics)
Objective: Pressure ulcers (PUs) are common and debilitating wounds that arise when immobilized patients cannot shift their weight. Treatment is expensive and recurrence rates are high. Pathophysiological mechanisms include reduced bulk and perfusion of chronically atrophic muscles as well as prolonged occlusion of blood flow to soft tissues from lack of voluntary postural shifting of body weight. This has suggested that PUs might be prevented by reanimating the paralyzed muscles using neuromuscular electrical stimulation (NMES). A review of the published literature over the past 2 decades is detailed.